2013
DOI: 10.5114/aoms.2013.33355
|View full text |Cite
|
Sign up to set email alerts
|

State of the art paper Comprehensive insight into immune regulatory mechanisms and vascular wall determinants of atherogenesis – emerging perspectives of immunomodulation

Abstract: For many years atherosclerosis was believed to be the passive accumulation of cholesterol in vessel walls. Today the picture is more complex, as immune processes occur in atherogenesis. Considerable attention is focused on the particular role of adaptive immune responses orchestrated by T cell subsets. Since the role of Th1/Th2 balance and Th1 cell domination in atherogenesis is already known, the involvement of regulatory T lymphocytes and recently described Th17 cells raises new concerns. On one hand, each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…As the consequence, local inflammation may shift from the acute phase to the chronic condition negative for the tissue and unfavorable for its recovery. This idea has been supported by the studies showing the presence of IL-4 at high levels in tissues of patients with chronic inflammatory diseases (25), including atherosclerosis (26,27). Yet, IL-33 was found to reduce atherosclerosis (28) and IL-33/ST2…”
Section: Accepted Manuscriptmentioning
confidence: 88%
See 1 more Smart Citation
“…As the consequence, local inflammation may shift from the acute phase to the chronic condition negative for the tissue and unfavorable for its recovery. This idea has been supported by the studies showing the presence of IL-4 at high levels in tissues of patients with chronic inflammatory diseases (25), including atherosclerosis (26,27). Yet, IL-33 was found to reduce atherosclerosis (28) and IL-33/ST2…”
Section: Accepted Manuscriptmentioning
confidence: 88%
“…axis is able to activate cardioprotective signaling pathways (23,(25)(26)(27). It was shown that IL-33 exacerbates DDS-induced experimental ulcerative colitis leading to diarrhea in mice.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…We monitored the most reliable indicator of endothelial function – flow-mediated dilatation [40]. In future it would be valuable to address some other biomarkers of endothelial health with all the limitations of these, including soluble adhesion molecules, ADMA and von Willebrand factor, as well as others [9, 4144]. Predominance of women in the study group could also be a limitation to the generalizability of the study findings; however, the study population is consistent with the epidemiology of DRS.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms which link oral inflammation and cardiovascular effects are not yet fully described, but one of the most important hypotheses is the preactivation of the immune system. Local inflammation in the oral cavity may trigger systemic inflammation, with the production of interleukin (IL)-6, C-reactive protein (CRP), tumour necrosis factor (TNF)-α and other proinflammatory cytokines [7, 8], as well as activation of a cellular immune response [9]. …”
Section: Introductionmentioning
confidence: 99%
“…An increased level of IL-17 has been reported in lungs of patients with severe asthma [4]. Studies also show that Th17 cells may participate in the pathogenesis of coronary heart disease and myocardial infarction by affecting atherosclerosis [5]. Interleukin-23, a heterodimeric cytokine consisting of a p19 subunit specific for IL-23 and a p40 subunit shared with IL-12, has been shown to play an important role in the maintenance [6] and acquisition of pathogenic function of Th17 cells [7].…”
Section: Introductionmentioning
confidence: 99%